2019
DOI: 10.3389/fnins.2018.01048
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Routine Clinical Measures to Inform Strategies for Better Hearing Performance in Cochlear Implant Users

Abstract: Neuroprostheses designed to interface with the nervous system to replace injured or missing senses can significantly improve a patient’s quality of life. The challenge remains to provide implants that operate optimally over several decades. Changes in the implant-tissue interface may precede performance problems. Tools to identify and characterize such changes using existing clinical measures would be highly valuable. Modern cochlear implant (CI) systems allow easy and regular measurements of electrode impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The resulting distribution of basal interface impedances computed from the apical distribution according to (17) is overlaid in Fig. 6 (bottom right, green) and shows acceptable agreement with the measured distribution.…”
Section: A Interface Impedance Distributionmentioning
confidence: 66%
See 1 more Smart Citation
“…The resulting distribution of basal interface impedances computed from the apical distribution according to (17) is overlaid in Fig. 6 (bottom right, green) and shows acceptable agreement with the measured distribution.…”
Section: A Interface Impedance Distributionmentioning
confidence: 66%
“…The implants perform telemetry measurements with charge balanced, rectangular biphasic cathodic-first pulses with an amplitude of I stim ≈ 300 µA and a pulse-width of 24 µs [16]. The voltage potential on the recording electrode is measured at the end of the anodic phase [17] with respect to a large ground electrode located on the implant body. A schematic drawing of the current stimulus and resulting voltage on the electrode is shown in Fig.…”
Section: B Implant Telemetrymentioning
confidence: 99%
“…CI failures may be due to device (hard) failure, soft failure, or surgical complications. Soft failure is a condition in which the implant device passes the integrity test but patients experience declining speech comprehension or non-auditory aversive symptoms [ 6 , 10 ]. In the present study, the “short circuits” condition was observed in half of the electrodes in both cases.…”
Section: Discussionmentioning
confidence: 99%
“…The CI device presents a sequence of current pulses, similar to those produced by the biological hearing system, via a platinum multi-electrode array located in the cochlea. It has been demonstrated that CI recipients typically experience improved speech comprehension and speech production ability [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor outcomes cannot always be explained, although successful outcomes are predominant. Today, cochlear implant hearing performance can be measured in situ, which is a relatively new research method and expected to improve the success rate of cochlear implants [ 54 , 55 ].…”
Section: Current Treatment Methodsmentioning
confidence: 99%